The Influence of Serving Leadership Style and Work Culture on Employee Performance at PT. Noor Abika Tours and Travel - Raden Fahri Ziaurrahman; Romat Saragih (Jurnal Indonesia Sosial Teknologi, 2024)
Every leader has a unique character and background, resulting in variations in their leadership style. These differences lead to diverse ways of influencing team members, known as leadership styles. This study aims to examine the impact of servant leadership and work culture on employee performance at the umrah and hajj service company, PT. Noor Abika Tours and Travel, after a leadership transition. The research method employed is quantitative, utilizing descriptive analysis and causal analysis. The sample in this study uses a saturated sample technique, involving the entire population, which consists of 54 employees of PT Noor Abika Tours and Travel. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 27. The results of the study indicate that the variables of servant leadership style, work culture, and employee performance are all in the very good category. The findings also show that servant leadership style and work culture have a positive and significant impact on employee performance, both partially and simultaneously.